Developing Illustrated Storybook with Local Characters for Financial Literacy Learning in Elementary Schools - Mohamad Ilham; Etriana Meirista; Fredy Fredy (STAI Hubbulwathan Duri, 2021)
This study aims at producing illustrated storybook using local characters that meet the eligibility criteria. Research and development (R D) were employed as the research design adopting the 4D models, consisting of four stages: defining, designing, developing, and disseminating. The defining includes need analysis, content analysis, and specification of objectives. The design contains preparation illustrated storybook, selecting characters, choosing story formats, and pre-designs. Developing involve expert validation on the material, language, media aspects and limited trials. Disseminate was carried out by distributing illustrated storybooks produced in several elementary schools in Merauke district, Papua Province. The results of expert validation and students’ responses indicate that the product developed has obtained the eligible category. Besides, the limited trial results to see the improvement of students’ understanding obtained by the n-gain value between the pretest and post-test were 0.51. It means improving students' understanding after using illustrated storybooks with local characters in the medium category.